Synthesis, molecular modeling, in vivo study, and anticancer activity of 1,2,4-triazole containing hydrazide-hydrazones derived from (S)-naproxen - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (WILEY-V C H VERLAG GMBH, 2019)
A new series of 1,2,4-triazole containing hydrazide-hydrazones derived from (S)-naproxen (7a-m) was synthesized in this study. The structures of these compounds were characterized by spectral (Fourier-transform infrared spectroscopy, H-1-nuclear magnetic resonance (NMR), C-13-NMR, and high-resolution electron ionization mass spectrometry) methods. Furthermore, molecular modeling of these compounds was studied on human methionine aminopeptidase-2. All synthesized compounds were screened for anticancer activity against three prostate cancer cell lines (PC3, DU-145, and LNCaP) using the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium colorimetric method. Compound 7a showed the best activity against the PC3, DU-145 and LNCaP cancer cell lines with IC50 values of 26.0, 34.5, and 48.8 mu M, respectively. Compounds 7b, 7k, and 7m showed anticancer activity against cancer cell lines PC3 and DU-145 with IC50 values of 43.0, 36.5, 29.3 mu M and 49.8, 49.1, 31.6 mu M, respectively. Compounds 7f and 7g showed anticancer activity against PC3 cells with IC50 values of 43.4 and 34.5 mu M, respectively. To assess the biodistribution in mice of IRDye800, dye-labeled compound 7a or 100 mu M of free dye was injected intravenously into the mice's tail. In vivo images were taken with in vivo imaging system spectrum device at 60, 120, 180, 240, 300, and 360 min after injection. At the end of 360 min, ex vivo studies were carried out to determine in which organs the dye was accumulated in the urogenital system. Ex vivo studies showed that the accumulation of compound 7a in the prostate is greater than that of the free dye, and it is concluded that compound 7a may be promising for the treatment of prostate cancer.
Keywords: (S)-naproxen; 1,2,4-triazole; hydrazide-hydrazone; methionine aminopeptidase; prostate cancer; DERIVATIVES; NAPROXEN; AGENTS; OVEREXPRESSION